Theoretical studies of comets in the 55 Cancri system. Issue 4 (18th June 2020) - Dvorak, Rudolf; Loibnegger, Birgit; Cuntz, Manfred
ABSTRACT: We present orbital integrations for various Jupiter family comets (JFCs) in the 55 Cancri system. This star is known to possess (at least) five planets with masses ranging from super-Earth to Jupiter-type. Furthermore, according to observational constraints, there is a space without planets between ∼0.8 and ∼5.7 au, offering the principal possibility of habitable terrestrial planets, including long-term orbital stability. Hence, there is a stark motivation for the study of comets in the 55 Cnc system noting that comets are viewed a viable candidate mechanism for the delivery of water to Earth-type planets located in stellar habitable zones. However, our study shows that the duration of stability of JFC analogues in the 55 Cnc system is much shorter compared to comets in the Solar system owing to profound differences in the planetary structure of the systems. For example, between planet 55 Cnc-f and 55 Cnc-d, the comets do not undergo close cometary encounters akin to the Earth and Mars in the Solar system as the planetary masses in the 55 Cnc system are much larger than in the Solar system and therefore the comets are much less orbitally stable. Nevertheless, we expect an increased number of comet–planet encounters as well as cometary collisions in the 0.8/5.7 au gap. Future observations and additional theoretical studies are required to shed light on the possibility of habitable terrestrial planets in the 55 Cnc system, including the possible role(s) of exocomets in the facilitation of planetary habitability.